Tinjauan Atas Prosedur Kas Masuk Dan Kas Keluar Pada Agria Hotel Bogor - Maharani, Biyas Cahaya; Nurjanah, Yayuk (Prodi Pariwisata dan LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
ABSTRACTA procedure is writing that contains steps or stages in doing something. These steps include a sequence of processes for making something from the beginning to the end with the aim of achieving or creating a goal. An organization has important procedures to ensure that there is no miscommunication at the organizational stage. Because in the end procedures will become guidelines for an organization to carry out activities within it, one of which is cash. Cash is an asset that requires special handling, especially in receiving and disbursing cash. Therefore, it is necessary to have a cash in and cash out procedure. The purpose of this research is to find out how the cash in and cash out procedures implemented at the Agria Hotel Bogor are in accordance with existing standard operational procedures or not. From the results of the review, it shows that the cash in and cash out procedures at the Agria Bogor Hotel are good. The existing procedures at the Agria Hotel are quite good, but there are still some procedures that are not in accordance with standard operational procedures. Because in the procedure there is a lack of adequate human resources. Therefore, existing procedures need to be improved in the future. Keywords: Procedures, Cash In, Cash Out